PRINCIPLES OF GOOD FAITH AND OBJECTIVE FUNCTION OF SOCIAL CONTRACT BEFORE THE CONTRACT OF PURCHASE AND SALE - Guarize, Daniela Ferrarini (2012)
This study aims to analyze the content of the principles of good faith and objective social function of contract, taking into account the purchase and sale. It is observed that these two principles, before the Civil Code of 2002 stemmed solely from case law, have now been inserted into Law 10.406/02, which highlights the new social context of the Brazilians. The aim is also in the present study, comment on how these two principles are applied by our courts and are understood by the doctrine. Still, it is noted that the principle of “pacta sunt servanda” ended up being relativized by the principles of good faith and objective of the social contract.